Wireless Sensor Network for Monitoring Maturity Stage of Fruit - M. Krairiksh; J. Varith; A. Kanjanavapastit (My University, 2011)
In this letter, we present a wireless sensor network for monitoring the maturity stage of fruit. A dual-polari- zation coupled patch sensor, which is robust to environmental changes, was designed to operate at 2.45 GHz. It was attached to a Durian fruit for a period of days to measure the magnitude of mutual coupling corresponding mainly to the starch concentration of its pulp. Signal was transmitted from a sensor node, via tree nodes, to a master node that displays the variations occurring in the period. The maximum mutual coupling occurred at the maturity stage of 60% whereas the minimum occurred at 70%. These results demonstrate that this wireless sensor network can enable fruit growers to harvest their Durians at an appropriate time, providing a reliable quality control for export.
Keywords: Sensor node; Spectroscopy and Chemometric Analyses